A Novel Approach to Plithogenic Neutrosophic Hypersoft Rough Set and Its Application to Decision Making Problem With Reference to Bakery Industry - Subha, V. S.; Selvakumar, R. (Communications in Mathematics and Applications, 2024)
The neutrosophic set, plithogenic hypersoft set, and rough set are distinct mathematical models to deal with different types of uncertainties in data and information. In this paper, we advance the study of plithogenic neutrosophic hypersoft rough set by combining plithogenic neutrosophic hypersoft set with rough set. Using plithogenic neutrosophic hypersoft rough set and the correspondence between objects, we develop an algorithm to solve a decision making problem occurring in Bakery industry. Finally a real life example is solved using the algorithm developed.